2017
DOI: 10.1016/j.renene.2017.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Survivability of wave energy converters using CFD

Abstract: The survivability of Wave Energy Converters (WECs) in extreme waves is a critical issue faced by developers; typically assessed via small scale physical experiments with considerable uncertainties. Until recently, confidence in the ability of numerical tools to reproduce extreme wave events and their interaction with floating structures has been insufficient to warrant their use in routine design processes. In this work a fully nonlinear, coupled tool for simulating focused wave impacts on generic WEC hull for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
89
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(91 citation statements)
references
References 28 publications
1
89
0
1
Order By: Relevance
“…The moments of inertia corresponding to the other two geometric axes, I xx and I yy are given relative to the CoM of each of the structures. Complimentary work involving Geometry 1 can be found in Hann et al (2015) and Ransley et al (2017). In all cases, the structure is taut-moored using the same linear spring mooring with a stiffness of 67 N/m and a rest length of 2.199 m. Table 2 gives some key parameters when the structure is at rest (z = 0 corresponds to the still water level).…”
Section: Test Casesmentioning
confidence: 99%
“…The moments of inertia corresponding to the other two geometric axes, I xx and I yy are given relative to the CoM of each of the structures. Complimentary work involving Geometry 1 can be found in Hann et al (2015) and Ransley et al (2017). In all cases, the structure is taut-moored using the same linear spring mooring with a stiffness of 67 N/m and a rest length of 2.199 m. Table 2 gives some key parameters when the structure is at rest (z = 0 corresponds to the still water level).…”
Section: Test Casesmentioning
confidence: 99%
“…The grid shown in Figure 5 was attained with grid resolution and convergence studies, including those reported in [2], an example of which is provided in Figure 6. The refined grid regions were established based on guidance from STAR-CCM+ [24], previously reported extreme sea state CFD studies [6,9,[25][26][27][28], accurately modeling the wave propagation, minimizing wave reflections, minimizing y+ on the RM3 model surface, and accurately resolving the velocity gradients around the model while keeping the total number of cells at a minimum. The final grid resolutions at the water surface and total number of cells for each case are reported in Table 3.…”
Section: Regular Wave Simulationsmentioning
confidence: 99%
“…(2011) and Deng et al (2016), Ransley (2015) has demonstrated that a similar approach can be applied to investigate the dynamic response of a floating moored structure. Such technique requires the time history of wave elevation at a point which is provided in this paper and in the Research Gate page of the first author 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 7 (Abdussamie, 2017).…”
mentioning
confidence: 99%